Identifying queer discourses and navigational strategies in mathematics for undergraduate STEM students - Voigt, Matthew (Frontiers in Education, 2024)
Introduction While research has explored racialized and gendered discourses in mathematics, there is a gap in understanding the experiences of Queer students and the discourses related to sexual identity in mathematics. This study aims to identify the discourses about mathematics that Queer STEM students describe in relation to their Queer identity and how they navigate these discourses. Methods Using phenomenology, individual interviews were conducted with 17 Queer STEM students at four universities in the United States. The interviews explored their life histories, experiences in mathematics, and responses to vignettes depicting mathematical scenarios. Grounded theory was leveraged to analyze the interviews to build a framework for Queer discourses and navigational strategies. Results Seven Queer discourses in mathematics were identified with underlying notions of exclusion and irrelevancy. The most prevalent discourses cast Queer identity as being irrelevant (erasure), unseen (heteronormative), or discriminated against (marginalized) in mathematics. At the same time there were some beliefs that Queer identity acceptance was unknown (ambiguous) was treated equally (normalized) or was accepted and even valued in math. Key findings from the study help theory build an exclusion-irrelevancy space to network together mathematical discourses and highlight how Queer marginalization is acted upon based on notions of rightful presence and not mathematical success. Discussion This study highlights the need to recognize and address the marginalization of Queer students in mathematics. By understanding the discourses and navigational strategies employed by these students, educators can create more inclusive and equitable STEM environments. It is critical to recognize and build upon the unique strengths of Queer students in mathematics, rather than focusing only on the challenges they face.